Determination of Competitive Priorities at Egyptian Garment Manufacturing - M, Seddik.K. (International Journal of Economics, Business and Management Studies, 2019)
Competitive priorities support many establishments to face challenges and share markets. Depending on several references, competitive priorities divided into five dimensions (Quality, Cost, Delivery, Flexibility, and innovation). In this article determination of competitive priorities at Egyptian garment manufacturing was investigated. The research, based on a designed questionnaire which offered to a sample of 50 respondents. Likert-scale was used to assess the respondents’ answers and the findings were analyzed by using Microsoft Excel. The samples encompassed 60.46% of export garment enterprises and 39.54% of domestic garment enterprises. The results clarified that quality was the highest priority while the cost was minimal. At the same time, the results showed that domestic garment enterprises (Group B) require more awareness in the implementation of competitive dimensions. Furthermore, the results revealed that, although some policies had a high level of execution, the lowest consistency was achieved (based on the variance coefficient) indicating a potential decline over time. The nature of markets influence on competitive priorities and its implementation at Egyptian garment enterprises. Adopting sophisticated cost policies is urgent for maintaining market share. Some policies need more improvements thru practicing, empowerment, and accountability to ensure the sustainability of competitiveness.